THE EFFECT OF COMBINED MARMET AND OXYTOCIN MASSAGE TO COLOSTRUM PRODUCTION AMONG SECTION CAESAREAN MOTHER - Barirah Barirah; Eti Mulyati; Norma Yunita (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Barriers to breastfeeding occurred on postpartum mother after section caesarean due to postoperative pain can inhibit nerve posterior pituitary gland that produces the hormone oxytocin that plays a role in the process of lactation. Marmet technique is one safe way that can be done to stimulate the breast to produce more milk, whilst oxytocin massage is conducted along the vertebrae to costae fifth, sixth and an attempt to stimulate the hormones prolactin and oxytocin after delivery. Aims: The objective of this study was to analyze the effect of marmet and oxytocin massage combination in improving colostrum production. Methods: The population in this study was a postpartum mother after 2 hours delivery. A total of 18 postpartum mothers were involved, divided into 9 treatments and 9 controls. Observations included viewing data on time measurements and the amount of colostrum secreted through the breast of the post-partum mother (instrument = syringe and spoon) and for measuring the oxytocin massage of the researcher using the oxytocin massage guide. Result: The average time of postpartum mothers in the intervention groups to produce colostrum after Marmet and massage techniques combined oxytocin (treatment group) was of 5.86 hours whilst mothers who do not receive any treatment able to produce after 5.89 hours. Statistical test results in getting P value = 0939, p value ie p> α (0.05), indicating there is no effect of the combination of massage techniques Marmet and oxytocin on colostrum production among post section caesarea mothers. Conclusions: Providing education for mothers and families is needed in order to support the production of colostrum sooner after birth.